Religious Education and Its Interaction with the Spiritual Dimension of Childhood: Teachers’ Perceptions, Understanding and Aspirations - Hill, Ellie (Religions, 2022)
In England, religious education (RE) is a part of the basic curriculum mandatory for all pupils in the compulsory years of schooling. This paper explores how RE and spirituality interact and whether one can contribute to the effective delivery of the other. It explores the experience of a small group of subject leaders working in schools in one local authority area in the West Midlands of England, drawn from schools with a religious affiliation and those without. Using in service training activities, questionnaires and reflective processes, it seeks to elicit their aspirations for the interaction between RE and spirituality (also referred to as meaning-making). The findings suggest the subject leaders have an intention to develop both activity to promote learning and activity to apply that learning to real life experience. This suggests that developing a spiritual dimension to religious education requires a move from the abstract or theoretical and from knowledge acquisition towards increased engagement, making a personal response and considering what difference can be made as a result. As such, a spiritual dimension to learning cannot be passive. The project has the potential to impact policy and practice on both national and international levels, given its focus on values and pedagogy rather than specific curriculum content.